Karjeros valdymas : organizacinė perspektyva : mokomoji knyga - Petkevičiūtė, Nijolė (Vytautas Magnus University, 2013)
Issues of development and management of career in organization are presented in this tutorial. The book analyses peculiarities of personal and organizational career; organizational entrance; first steps and activities in organization; personnel needs and possibilities of career development in organization; stages of career and their tasks; talents and their influence on career management; possibilities and their use in career development; roles of career of employees and issues of their development. The tutorial is dedicated to students and leaders and employees of various organizations. Mokomojoje knygoje pristatomi karjeros organizacijose vystymo ir valdymo klausimai. Knygoje nagrinėjama asmeninės ir organizacinės karjeros ypatumai; pirmieji žingsniai ir veiklos organizacijoje; darbuotojų poreikiai ir karjeros vystymo galimybės organizacijoje; karjeros etapai ir jų uždaviniai; talentai ir jų įtaka karjeros valdymui; galimybės ir jų panaudojimas karjeros plėtroje bei darbuotojų karjeros vaidmenys ir jų vystymo klausimai. Mokomoji knyga skiriama studentams bei įvairių organizacijų vadovams ir darbuotojams.